The Effects of International Financial Reporting Standards Implementation on the Financial Performance and Position of Businesses in Developing Countries: Evidence from Kosovo - PERJUCI, Edona; HOTI, Arber (International Journal of Applied Economics, Finance and Accounting, 2022)
The International Financial Reporting Standards (IFRS), which are now used in many countries around the world, are an important step in the international development of financial reporting and auditing as they create international harmonization and a common language of financial reporting and accounting between companies and countries. Given Kosovo's recent adoption of IFRS, the purpose of this study is to undertake an empirical examination of the implementation of IFRS for enterprises that are legally obliged to comply with these standards. The research quantifies the impact of these standards on the actual performance and financial position ratios of the businesses examined by comparing periods before and after the implementation of IFRS. Research findings suggest that the adoption and implementation of IFRS did not affect the profitability and returns of businesses. In the contrary, long-term solvency and stability of businesses in Kosovo was affected by the implementation of IFRS. Additionally, there was an influence on the short-term solvency and liquidity of firms in Kosovo during the pre- and post-adoption periods of IFRS.